The basic genetic toolkit to move in with your photosynthetic partner - Reyes-Prieto, Adrian (Frontiers in Ecology and Evolution, 2015)
The origin of photosynthetic organelles via endosymbiosis more than 1 Gya ago was a major detonator of eukaryotic diversification. The evolution of a stable endosymbiotic relationship between eukaryotic cells and photosynthetic cyanobacteria involved series of cellular and molecular processes that are not entirely understood. Critical steps towards the evolution of plastids occurred when the host cell gained genetic and metabolic control over the captured cyanobacterium. Proteins recruited from the host repertoire had major roles initiating the metabolite exchange between both symbiotic partners. Concurrently, the relocation of certain cyanobacterial genes into the host nuclear genome was critical to coordinate the division of the endosymbiotic cells and the transit of nuclear-encoded proteins into the novel organelle. This review explores diverse studies that have identified key “endosymbiosis genes” and discusses the putative roles of the encoded proteins during the early evolution of plastids. The understanding of the regulation mechanisms and functions of the “endosymbiosis genes” will shed light on the design of genetic engineering approaches to facilitate endosymbiotic associations.